(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article analyzes the identification of the most effective linguistic and cultural methods of terms in the translation of clothing and fashion design. The traditional classification of features of term formation includes several types: morphological methods, syntactic method of term formation, and morphological and syntactic methods.